2003
DOI: 10.1101/gad.254903
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotides responsible for the direct physical contact between the chromatin insulator protein CTCF and theH19imprinting control region manifest parent of origin-specific long-distance insulation and methylation-free domains

Abstract: The repression of the maternally inherited Igf2 allele has been proposed to depend on a methylation-sensitive chromatin insulator organized by the 11 zinc finger protein CTCF at the H19 imprinting control region (ICR). Here we document that point mutations of the nucleotides in physical contact with CTCF within the endogenous H19 ICR lead to loss of CTCF binding and Igf2 imprinting only when passaged through the female germline. This effect is accompanied by a significant loss of methylation protection of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
145
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(156 citation statements)
references
References 26 publications
10
145
1
Order By: Relevance
“…A novel finding in our study was the C/T polymorphism identified by the endonuclease, HhaI, in CTCF binding site 6. It is thought that the number of functional CTCF binding sites in the DMR correlates with their insulator activity and this C/T SNP could influence the stability of the binding to the unmethylated allele in this critical imprinting control region (45). The comparison of the genotypes, CC and CT + TT, in the 95 patients with cancer and in the 157 volunteers revealed a statistical trend towards a lower frequency of the homozygous wild-type CC genotype in the cancer group.…”
Section: Discussionmentioning
confidence: 98%
“…A novel finding in our study was the C/T polymorphism identified by the endonuclease, HhaI, in CTCF binding site 6. It is thought that the number of functional CTCF binding sites in the DMR correlates with their insulator activity and this C/T SNP could influence the stability of the binding to the unmethylated allele in this critical imprinting control region (45). The comparison of the genotypes, CC and CT + TT, in the 95 patients with cancer and in the 157 volunteers revealed a statistical trend towards a lower frequency of the homozygous wild-type CC genotype in the cancer group.…”
Section: Discussionmentioning
confidence: 98%
“…We can therefore conclude that the CTCF insulator binding sites are dispensable for the maintenance of ICR hypomethylation in female germ cells and for the acquisition and maintenance of ICR hypermethylation in male germ cells. Thus, the binding of CTCF, or another protein which recognizes the site, e.g., the "brother of the regulator of imprinted sites" (BORIS) protein (20,26), is not required in either of these processes. With respect to what other ICR sites might be involved, we have identified a set of conserved nuclear hormone receptor-like sites in the ICR which show in vivo footprints in somatic cells and which can bind proteins specifically in male fetal germ cell nuclear extracts in EMSAs (41a.…”
Section: Discussionmentioning
confidence: 99%
“…1B to D). We would also expect this mutation to fully eliminate binding of CTCF to the ICR in vivo; it was shown that changing the mouse CTCF insulator binding site core sequence from CCGC(G/A)(T/C)GG(T/C)GGCAG to CCGCG(G/A)(T/C)AT ATGCAG was sufficient to eliminate all CTCF binding to the ICR in vivo at the level of detection of chromatin immunoprecipitation assays (26). In comparison, our mutation involved changing the three invariant nucleotides of these same four nucleotides: three G3T, four other invariant nucleotides, two C3A and two G3T, and two other nucleotides, (G/A)3T and (T/C)3G, to give CATA TGTTTTTCAG (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the H19 ICR, CTCF binding might prevent methylation in the female germline. (37,38) However, it is not known whether, in the male germline, methylation is put onto the ICR by default, or via an active recruitment process. It remains unknown also, which mechanism(s) dictates the establishment of methylation at the KvDMR1 specifically in the female germline.…”
Section: Introductionmentioning
confidence: 99%